Do Corticosteroid Injections for the Treatment of Pain Influence the Efficacy of mRNA COVID-19 Vaccines?. Issue 4 (19th February 2021) - Lee, Haewon; Punt, Jennifer A; Miller, David C; Nagpal, Ameet; Smith, Clark C; Sayeed, Yusef; Patel, Jaymin; Stojanovic, Milan P; Popescu, Adrian; McCormick, Zachary L; ,
Abstract: Myth: Corticosteroid injection for the treatment of pain and inflammation is known to decrease the efficacy of the messenger ribonucleic acid (mRNA) vaccines for coronavirus disease 2019 (COVID-19). Fact: There is currently no direct evidence to suggest that a corticosteroid injection before or after the administration of an mRNA COVID-19 vaccine decreases the efficacy of the vaccine. However, based on the known timeline of hypothalamic-pituitary-adrenal (HPA) axis suppression following epidural and intraarticular corticosteroid injections, and the timeline of the reported peak efficacy of the Pfizer-BioNTech and Moderna vaccines, physicians should consider timing an elective corticosteroid injection such that it is administered no less than 2 weeks prior to a COVID-19 mRNA vaccine dose and no less than 1 week following a COVID-19 mRNA vaccine dose, whenever possible.